2002
DOI: 10.1046/j.1444-2906.2002.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the digestive tract of wild ayu

Abstract: The gut and gut contents of ayu Plecoglossus altivelis caught in the Ohta River in Hiroshima prefecture, Japan were examined. Relative intestine length (intestine length/body length) was almost constant. Except for relative intestine length, characteristics of the gut of wild ayu were not significantly different from those of cultured ayu. The height of intestinal folds increased and their width declined from stomach to anus. Cyanobacteria (Homoeathrix sp. and Calothrix sp.) and diatoms (Cymbella s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
(15 reference statements)
0
7
0
1
Order By: Relevance
“…As far as is known, the pyloric caecae of cobia juveniles and adults has not been described and although a detailed description is beyond the scope of this study a few general observations were made regarding this structure. In juvenile fish, the gross morphology of the pyloric caecae resembled that described for Ayu Plecoglossus altivelis (Temminck & Schlegel) (Nakagawa et al, 2002) in which several 'stalks' emanated from the proximal end of the AI each branching multiple times to form numerous blind sacs. The number of caecae increased as cobia increased in size and appeared to number in the thousands in adult fish.…”
Section: Discussionmentioning
confidence: 58%
“…As far as is known, the pyloric caecae of cobia juveniles and adults has not been described and although a detailed description is beyond the scope of this study a few general observations were made regarding this structure. In juvenile fish, the gross morphology of the pyloric caecae resembled that described for Ayu Plecoglossus altivelis (Temminck & Schlegel) (Nakagawa et al, 2002) in which several 'stalks' emanated from the proximal end of the AI each branching multiple times to form numerous blind sacs. The number of caecae increased as cobia increased in size and appeared to number in the thousands in adult fish.…”
Section: Discussionmentioning
confidence: 58%
“…The trophic habits of most sicydiine gobies are undescribed, but where known, these fishes often rapidly become herbivores when they settle in fresh waters (Schoenfuss et al 1997;Fitzsimons et al 2003), and they feed by grazing periphyton from the stream substrate. In so doing, they avoid the problem of finding enough small-sized animal foods-herbivory is especially well known in some of the speciose sicydiine gobies, and is also true of the Japanese ayu (Plecoglossus-f. Osmeridae; Nakagawa et al 2002;Abe et al 2007) and the Australian and New Zealand so-called graylings (genus Prototroctes-f. Prototroctidae; McDowall 1976McDowall , 1990, all of which are amphidromous.…”
Section: Risks and Benefits Of An Amphidromous Life Cyclementioning
confidence: 99%
“…Alves and Tom e (1966) observed in Scomberomorus cavalla that pyloric caeca show different levels of development, which was also observed in M. furnieri, whose caecum showed projections of different sizes and thickness. Nakagawa et al (2002) reported larger number of caeca with the ontogenetic development of the herbivore Plecoglossus altivelis. Pyloric caeca are histologically similar to the intestines, presenting villi that increase the surface available for absorption and secretion, but also work as a food reservoirs.…”
Section: Discussionmentioning
confidence: 94%
“…Nakagawa et al . () reported larger number of caeca with the ontogenetic development of the herbivore Plecoglossus altivelis . Pyloric caeca are histologically similar to the intestines, presenting villi that increase the surface available for absorption and secretion, but also work as a food reservoirs.…”
Section: Discussionmentioning
confidence: 96%